2018
DOI: 10.1186/s13229-018-0225-5
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates prenatal progestin exposure-induced autism-like behavior through ERβ activation

Abstract: BackgroundRecent literatures indicate that maternal hormone exposure is a risk factor for autism spectrum disorder (ASD). We hypothesize that prenatal progestin exposure may counteract the neuroprotective effect of estrogen and contribute to ASD development, and we aim to develop a method to ameliorate prenatal progestin exposure-induced autism-like behavior.MethodsExperiment 1: Prenatal progestin exposure-induced offspring are treated with resveratrol (RSV) through either prenatal or postnatal exposure and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 58 publications
6
61
0
Order By: Relevance
“…All data collection and analyses were performed randomly by experimenters blinded to the genotypes. The sample sizes are similar to those of previous publications (Huang et al, 2016(Huang et al, , 2019Xie et al, 2018) and listed in the figure legends. Data are represented as the means ± standard deviation (SD), and statistical analysis included the Chi squared test, non-parametric Mann-Whitney U test (for data that failed normality test), unpaired t-test, two-way ANOVA, and two-way repeated-measures ANOVA with post hoc Bonferroni multiple comparisons test were performed using SPSS 19.0 software (SPSS Inc., United States).…”
Section: Discussionsupporting
confidence: 83%
“…All data collection and analyses were performed randomly by experimenters blinded to the genotypes. The sample sizes are similar to those of previous publications (Huang et al, 2016(Huang et al, , 2019Xie et al, 2018) and listed in the figure legends. Data are represented as the means ± standard deviation (SD), and statistical analysis included the Chi squared test, non-parametric Mann-Whitney U test (for data that failed normality test), unpaired t-test, two-way ANOVA, and two-way repeated-measures ANOVA with post hoc Bonferroni multiple comparisons test were performed using SPSS 19.0 software (SPSS Inc., United States).…”
Section: Discussionsupporting
confidence: 83%
“…We have previously found that prenatal progestin exposure suppresses ERβ expression in the amygdala instead of in other brain areas and subsequently contributes to ASD development in offspring, with male offspring being more susceptible than females. Additionally, ERβ overexpression in the amygdala significantly restores prenatal progestin exposure-induced ALB Xie et al, 2018), and maternal diabetesinduced autistic offspring show significant SOD2 suppression in the amygdala as well (Wang et al, 2019). Our results indicate that gene expression in the amygdala plays an important role in ASD development.…”
Section: Prenatal-dht Exposure-mediated Gene Expression In Autistic Omentioning
confidence: 57%
“…The DHT treatment was used to mimic PCOS conditions during the in vivo rat experiments (Mannerås et al, 2007;Noroozzadeh et al, 2017;Paixão et al, 2017). Our results show that prenatal DHT exposure induces ALB in offspring with suppressed expression of ERβ and SOD2 in the amygdala Li et al, 2018;Xie et al, 2018). AR knockdown partly diminishes this effect, indicating that DHT induces ALB through the AR signaling pathway.…”
Section: Prenatal Dht Exposure-mediated Autism-like Behaviormentioning
confidence: 76%
See 2 more Smart Citations